ANALISIS KINERJA KEUANGAN DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN PADA BANK GO PUBLIC - Irhamna Arma atush; Jeni Susyanti; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT The research conducted is about the analysis of financial performance and corporate social responsibility (CSR) on the value of the company at banks in Malang. The purpose of this study is to determine the influence of financial performance and CSR on the value of banking companies partially or simultaneously. The independent variable in this study is the financial performance measured using ROA, ROE, and NPM as well as corporate social responsibility (CSR) variables. While the dependent variable is the value of a banking company. There are 15 banking companies in Malang, 9 of which are used as research samples with financial statements of banking companies in 2016 - 2018. The analysis used is multiple linear regression analysis and several tests, including classic assumption tests (normality, multicollinearity, autocorrelation, and heteroscedasticity) and hypothesis testing (t test and F test). The results of this study mention financial performance (ROA, ROE, NPM) does not have an influence either partially or simultaneously on the value of banking companies. Corporate social responsibility (CSR) has no influence on the value of the company either partially or simultaneously.Keywords: ROA, ROE, NPM, CSR, and company value.